Impact of Haemonchus contortus infection on feed intake, digestion, liveweight gain, and enteric methane emission from Red Maasai and Dorper sheep - Mwangi, Paul; Eckard, Richard; Gluecks, Ilona V.; Merbold, Lutz; Mulat, Daniel; Gakige, Jesse K.; Pinares-Patino, Cesar S.; Marquardt, Svenja (Frontiers Media, 2023)
A study was conducted with Red Maasai and Dorper lambs to evaluate the effects of infection with the gastrointestinal nematode (GIN) Haemonchus contortus on feed intake, liveweight gain (LWG), feed energy and nitrogen partitioning, and enteric methane (CH4) emissions. Six- to seven-month-old Red Maasai (n=12) and Dorper (n=12) lambs were randomly allocated to three treatments (n=8, four lambs per breed) in a 2×3 factorial cross-over study over two periods (P1 and P2) of 36 days each. The treatments consisted of three combinations of GIN infection and feeding level: Infected + ad libitum feeding (I-adlib), uninfected + ad libitum feeding (Un-adlib), and uninfected + restricted feeding (Un-restd), across the two breeds. Lambs in the I-adlib group were trickle-infected daily with 1,000 L3 stage larvae of H. contortus for four consecutive days (Days 1–4), whereas lambs in the other experimental treatments were kept GIN free. The feed intake was measured daily. Liveweight (LW), faecal egg counts (FEC), and packed cell volume (PCV) were measured on Day 1 and weekly thereafter. On Days 29–33 total faecal and urine outputs were determined in metabolic crates. The lambs were then housed in respiration chambers for three consecutive days (Days 34–36). There was a washout period of 21 days before P2 started. Uninfected lambs (Un-adlib and Un-restd) had undetectable FEC throughout the study. On Day 36, FEC did not differ between the breeds (P>0.05). Infected lambs (I-adlib) had lower PCV than uninfected (Un-adlib and Un-restd) lambs on day 36. Neither breed nor infection influenced feed and nutrient intake, but as expected, restricted-fed lambs had a lower intake (P<0.05). The LWG of Un-adlib lambs was significantly higher than that of I-adlib and Un-restd lambs (P<0.05), whereas there was no breed difference (P>0.05). Neither breed nor infection affected feed digestibility, nitrogen retention or energy metabolisability (P>0.05). However, feed restriction decreased feed intake, LWG and N retention, whereas feed digestibility and energy metabolisability were unaffected. Neither daily CH4 emissions nor yield (per unit of feed intake) were affected by experimental infection, but Un-restd lambs had lower CH4 emissions per day. Red Maasai lambs had consistently lower daily CH4 emissions and yields than Dorper (P<0.01). This study confirmed the relative resistance of indigenous sheep (Red Maasai) to H. contortus infection, but the increased CH4 emission and yield due to GIN observed in other studies was not confirmed. Further investigations are needed to test whether in environments with multiple stress factors, local or indigenous breeds or their crossbreeds with exotic breeds may be better equipped to sustain production and simultaneously have a reduced carbon footprint than purebred exotic breeds.